2016
DOI: 10.1016/j.ceb.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Wound repair: a showcase for cell plasticity and migration

Abstract: A skin wound requires several cell lineages to exhibit considerable plasticity as they migrate towards and over the site of damage to contribute to repair. The keratinocytes that re-epithelialize the tissue, the dermal fibroblasts and potentially other mesenchymal stem cell populations that repopulate damaged connective tissue, the immune cells that counter infections, and endothelial cells that re-establish blood supply and facilitate the immune response -all of these cells are "dynamic" in that they are acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 82 publications
2
144
0
1
Order By: Relevance
“…41 As part of our in vitro characterization effort, we performed functional studies using MFs and HFs. These showed that P311 stimulated smooth muscle actin production, increased proliferation, promoted migration, and increased contractility of both MFs and HFs, all consistent with induction of the activated state 49 and the transition to myofibroblasts. 50 In addition, P311 had an antiapoptotic effect in both cell types.…”
Section: Discussionsupporting
confidence: 53%
“…41 As part of our in vitro characterization effort, we performed functional studies using MFs and HFs. These showed that P311 stimulated smooth muscle actin production, increased proliferation, promoted migration, and increased contractility of both MFs and HFs, all consistent with induction of the activated state 49 and the transition to myofibroblasts. 50 In addition, P311 had an antiapoptotic effect in both cell types.…”
Section: Discussionsupporting
confidence: 53%
“…During wound healing process, the portion of collagen increases with time, and by two weeks their fibers dominate the ECM. Phagocytic cells slightly disappear and the granulation tissue is progressively constituted by a denser and less vascularized tissue, located right under the regenerated epidermis [59]. Collagen degradation initiates early and is more active during inflammatory process.…”
Section: Wound Healing Phasesmentioning
confidence: 99%
“…The cells proliferation phase happens over the 5th to 14th days and initiates the repair process of both dermis and epidermis [59]. It is crucial for the formation of granulation tissue, which is a combination of cell elements, including fibroblasts, inflammatory cells, and endothelial components of ECM, such as fibronectin, glycosaminoglycans, and collagen.…”
Section: Wound Healing Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysfunction of skin homeostasis usually result in dire consequences, involving acute, chronic inflammation or infected wounds [3,4]. And skin wound healing is an intrinsic self-saving chain reaction, which is crucial to facilitate the replacement of damaged or lost tissues.…”
Section: Introductionmentioning
confidence: 99%